Balance Scorecard dalam Mengukur Kinerja Perusahaan PT Pertamina (PERSERO) - Lufriansyah Lufriansyah (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
the research conducted by the author aims to determine and analyze the company's financial and non-financial performance by analyzing the company's performance measurement of PT Pertamina (Persero) based on an approach with the Balanced Scorecard. The research approach uses a descriptive approach, with the object of research seen from the 2014-2018 financial statements of PT Pertamina (Persero). The research results show that large corporate debt occurs due to the large need for company operational costs, as well as the use of company debt used for additional The company's fixed assets are also financed by using company debt, the number of customers and employees is known that the performance of PT. Pertamina (Persero) tends to decrease which is considered not enough, and can be categorized as not so good, the performance measurement of PT. Pertamina (Persero) based on the approach with the Balanced Scorecard tends to experience a decrease as measured using the financial perspective, customer perspective, internal business process perspective and learning and growth perspective has decreased